Miltilateral Tariff Cooperation During the Formation of Customs Unions - Kyle Bagwell; Robert W. Staiger (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
We study the implications of customs union formation for multilperation. We model copperation in multilateral trade policy as self-enforcing, in that it involves balancing the current gains from deviating unilaterally from an agreed-upon trade policy against the future losses from forfeiting the benefits of multilateral cooperation that such a unilateral defection would imply. The early stages of the process union formation are shown to alter this dynamic incentive constraint in a way that leads to a temporary "honeymoon" for liberal multilateral trade policies. We find, however, that the harmony between customs unions and multilateral liberalization is temporary: Eventually, as the full impact of the emerging customs union becomes felt, a less favorable balance between current and future conditions reemerges, and the liberal multilateral polices of the honeymoon phase cannot be sustained. We argue that this is compatible with the evolving implications of the formation of the European Community customs union for the ability to sustain liberal multilateral trade policies under the General Agreement on Tariffs and Trade.
Keywords: 330